Making Sense of Hospital Project MisPerformance: Over Budget, Late, Time and Time Again—Why? And What Can Be Done About It? - Love, Peter; Ika, L.A. (2022)
Hospital projects worldwide often experience misperformance, showing a tendency to exceed their estimated cost, miss their deadline, suffer quality problems, and yield benefit shortfalls. Considering this ubiquitous problem, this paper aims to make sense of this phenomenon by addressing the following research question: How can we make sense of hospital project misperformance, and what can be done to mitigate its occurrence? We use an illustrative case study approach and the analytical lens of sense-making to examine the misperformance of three mega-hospital projects. Our research reveals issues such as scope changes, an inability to adapt and respond to risk and uncertainty, ineffectual project management and governance, and optimism bias, which combine to impact project performance adversely. We suggest that the two prominent theoretical perspectives dominating the literature in this field fall short of adequately explaining hospital project misperformance. We provide suggestions for improving the procurement process of hospitals and submit there is a need to develop a robust and balanced theory of project misperformance.